Kajian Pengeringan dan Pendugaan Umur Simpan Seledri pada Berbagai Bahan Kemasan Fleksibel - Tri Yulni; Rokhani Hasbullah; Leopold Oscar Nelwan (PERTETA, 2017)
AbstractCelery is a perishable horticultural product due to its high water content. This condition leads to a short durability of the celery, thus efforts to prolong its shelf life are required. This study aimed at studying the effects of immersion in sodium metabisulphite and drying temperature on the quality of dried celery leaves, and determining its shelf life using acceleration method based on critical moisture content approach. The results showed that soaking treatment using solution of sodium metabisulphite prior to drying process was able to maintain the dried celery leaves qualities, which resulted in higher chlorophyll content, lower apparent density, higher rehydration ratio, and higher VRS (volatile reducing substance) in comparison without soaking treatment. Moreover chlorophyll content, apparent density, volatile reducing substance (VRS), and rehydration behaviours were affected by the drying temperature. Shelf life of dried celery leaves based on critical moisture content approach represented in linear low density polyethylene (LLDPE) plastic, polypropylene (PP), and aluminium foil oriented polypropylene (OPP) were 30, 51, and 790 days, respectively. AbstrakSeledri merupakan produk hortikultura yang mudah rusak karena memiliki kandungan air yang tinggi. Kondisi ini menyebabkan seledri tidak tahan lama disimpan sehingga diperlukan penanganan untuk memperpanjang umur simpannya. Tujuan penelitian ini adalah mengkaji pengaruh perendaman dalam larutan natrium metabisulfit dan suhu pengeringan terhadap mutu daun seledri kering dan menentukan umur simpan daun seledri kering berdasarkan metode akselerasi dengan pendekatan kadar air kritis. Hasil penelitian menunjukkan perendaman dalam larutan natrium metabisulfit sebelum pengeringan mampu mempertahankan mutu daun seledri kering, dimana dihasilkan kandungan klorofil lebih tinggi, densitas kamba lebih rendah, rasio rehidrasi lebih tinggi, serta kandungan VRS lebih tinggi dibandingkan seledri tanpa perlakuan perendaman. Selain kandungan klorofil, nilai densitas kamba, VRS, dan rasio rehidrasi dipengaruhi oleh suhu pengeringan. Umur simpan seledri berdasarkan metode akselerasi dengan pendekatan kadar air kritis didapat dalam kemasan LLDPE, PP, dan aluminium foil OPP berturut-turut adalah 30, 51, dan 790 hari.